VEGFR1 promotes cell migration and proliferation through PLCγ and PI3K pathways. (December 2018) - Weddell, Jared; Chen, Si; Imoukhuede, P.
Abstract The ability to control vascular endothelial growth factor (VEGF) signaling offers promising therapeutic potential for vascular diseases and cancer. Despite this promise, VEGF-targeted therapies are not clinically effective for many pathologies, such as breast cancer. VEGFR1 has recently emerged as a predictive biomarker for anti-VEGF efficacy, implying a functional VEGFR1 role beyond its classically defined decoy receptor status. Here we introduce a computational approach that accurately predicts cellular responses elicited via VEGFR1 signaling. Aligned with our model prediction, we show empirically that VEGFR1 promotes macrophage migration through PLCγ and PI3K pathways and promotes macrophage proliferation through a PLCγ pathway. These results provide new insight into the basic function of VEGFR1 signaling while offering a computational platform to quantify signaling of any receptor. Thought experiment: discovered the protein functions with mathematics Many diseases and cancers have the potential to be prevented or cured with treatments that manage the function of specific biological proteins. Developing successful treatments are made difficult due to a lack of understanding of the function of these biological proteins, especially since they can have different functions depending on the type of cell they are functioning in. In this study,  Prof. Imoukhuede and his team from University of Illinois at Urbana-Champaign develop a mathematical approach to understand the overall function of such biological proteins. They apply this approach to a specific biological protein, which is poorly understood, to identify its basic function and discuss why its function may be different in different cells. Overall, this work provides an approach to direct disease treatment development by providing a better understanding of proteins driving the disease.